METHODOLOGICAL PECULIARITIES OF MILITARY FINANCIERS TRAINING ON THE EXAMPLE OF TEACHING SPECIAL SUBJECTS ON THE SPECIFICS AND PECULIARITIES OF THE ORGANIZATION OF COMPENSATION OF EMPLOYEES OF THE ARMED FORCES OF UKRAINE - Diachenko, I. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2020)
The scientific article reveals the purpose and meaning, subject and content (knowledge, skills, abilities) of the discipline «Compensation of military unit employees», its place in the system of specialists training of accounting specialties. The value of the discipline is to provide fundamental knowledge and practical skills in the organization of remuneration of labour, to teach how to charge and pay wages correctly and timely to employees of the Armed Forces of Ukraine, to be able to analyze expenses related to compensation of employees of the Armed Forces of Ukraine. The task of this discipline is to form and develop general and professional competencies in this field, to train fully developed, qualified and competitive military specialists capable of carrying out financial and economic activities of the military unit.It has been established that in today's conditions, in order to ensure quality education in military higher education institutions, special attention must be paid to the introduction of advanced pedagogical technologies in the educational process. Accounting disciplines, unlike many other economic disciplines, are based on events that are changing rapidly. Therefore, in order to form a high-quality military financier, the main emphasis in teaching accounting should not be on mechanical memorization of educational material, but on the development of thinking. The question of the close relationship between theory and practice is relevant nowadays.
Keywords: accounting disciplines, labor remuneration, military financier